If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(x + 6) = -24 Reorder the terms: 3x + -2(6 + x) = -24 3x + (6 * -2 + x * -2) = -24 3x + (-12 + -2x) = -24 Reorder the terms: -12 + 3x + -2x = -24 Combine like terms: 3x + -2x = 1x -12 + 1x = -24 Solving -12 + 1x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 1x = -24 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = -24 + 12 1x = -24 + 12 Combine like terms: -24 + 12 = -12 1x = -12 Divide each side by '1'. x = -12 Simplifying x = -12
| 11q-145=13 | | 4(v-4)=6v-22 | | (-7)-0= | | 0.09xX=43.43 | | 3+7=-11+2x | | -3+5(8+6)=37 | | 5bx^2-7ax=0 | | 3cosx-2=7 | | 6(m-2)+14=3(m+2)-6 | | -369+3x=12x+153 | | 2(x+7)=28-18-3(6-x) | | 0.09xX=57.51 | | x/.4-2x | | 21a-12=72 | | 2x+224=11x-10 | | 2ax-x-2ax= | | -215=5x+5(-3x-23) | | -14+x=35 | | 240/92 | | h(x)=32-8x | | 1/5r=2/2/3 | | 5x+5=-103-ux | | 1/2x=3/7/15 | | -3x-15=1/4x-2 | | 6(4x+10)= | | -2(6x-8)=-56 | | (-6+7p)=164 | | 1/6*k=-11 | | -4=4v+8 | | Log(5)*125=3x+2 | | 6/4÷-4 | | y=-16x^2+32x+100 |